Compensation to Ex-Wives for Domestic Violence in Indonesia - Asmuni, Asmuni (Hukum Keluarga Islam IAIN LANGSA, 2024)
This paper examines divorce lawsuits caused by domestic violence committed by husbands against wives, focusing on the rights of women as victims. In such cases, wives can file for divorce and demand compensation for the physical and psychological harm they have suffered. The study employs a qualitative approach with an analytical descriptive method, using the library method to gather and analyze both primary and secondary literature, including legal documents, laws, scientific articles, and case reports. The research aims to identify patterns, challenges, and solutions related to legal protection for victims of domestic violence in divorce proceedings. The findings reveal that while there are legal provisions for compensation, significant challenges remain, such as social stigma, economic dependence, and limited access to legal resources, which complicate women's ability to claim their rights. Additionally, societal attitudes and gaps in law enforcement further hinder the realization of justice for victims. The study concludes that public awareness campaigns and stronger advocacy are essential to empowering women and ensuring their rights are protected throughout the divorce process. It also emphasizes the need for stricter law enforcement to hold perpetrators accountable and provide justice for victims. This research contributes to improving legal and social frameworks for the protection of women facing domestic violence.